IMMOBILIZATION OF STRONTIUM DURING IRON BIOMINERALIZATION COUPLED TO DISSIMILATORY HYDROUS FERRIC OXIDE REDUCTION - Roden E.E.; Leonardo M.R.; Ferris F.Grant (My University, 2002)
The potential for incorporation of strontium (Sr) into biogenic Fe(II)-bearing minerals formed during microbial reduction of synthetic hydrous ferric oxide (HFO) was investigated in circumneutral bicarbonate-buffered medium containing SrCl2 at concentrations of 10 μM, 100 μM, or 1.0 mM. CaCl2 (10 mM) was added to some experiments to simulate a Ca-rich groundwater. In Ca-free systems, 89 to 100% of total Sr was captured in solid-phase compounds formed during reduction of 30 to 40 mmol Fe(III) L−1 over a 1-month period. A smaller fraction of total Sr (25 to 34%) was incorporated into the solid phase in cultures amended with 10 mM CaCl2. X-ray diffraction identified siderite and ferroan ankerite as major end products of HFO reduction in Ca-free and Ca-amended cultures, respectively. Scanning electron microscopy–energy dispersive x-ray spectroscopy revealed the presence of Sr associated with carbonate phases. Selective extraction of HFO reduction end products indicated that 46 to 100% of the solid-phase Sr was associated with carbonates. The sequestration of Sr into carbonate phases in the Ca-free systems occurred systematically according to a heterogeneous (Doerner-Hoskins) partition coefficient (DD-H) of 1.81 ± 0.15. This DD-H value was 2 to 10 times higher than values determined for incorporation of Sr (10 μM) into FeCO3(s) precipitated abiotically at rates comparable to or greater than rates observed during HFO reduction, and fivefold higher than theoretical partition coefficients for equilibrium Fe(Sr)CO3 solid solution formation. Surface complexation and entrapment of Sr by rapidly growing siderite crystals (and possibly other biogenic Fe(II) solids) provides an explanation for the intensive scavenging of Sr in the Ca-free systems. The results of abiotic siderite precipitation experiments in the presence and absence of excess Ca indicate that substitution of Ca for Sr at foreign element incorporation sites (mass action effect) on growing FeCO3(s) surfaces can account for the inhibition of Sr incorporation into the siderite component of ankerite formed in the Ca-amended HFO reduction experiments. Likewise, substitution of Fe(II) for Sr may explain the absence of major Sr partitioning into the calcite component of ankerite. The findings indicate that under appropriate conditions, sequestration of metals in siderite produced during bacterial Fe(III) oxide reduction may provide a mechanism for retarding the migration of Sr and other divalent metal contaminants in anaerobic, carbonate-rich sedimentary environments.